2017
DOI: 10.33087/jmas.v2i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lingkungan Kerja Dan Kompetensi Terhadap Motivasi Kerja Serta Dampaknya Terhadap Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Tanjung Jabung Timur

Abstract: The purpose of this research is to gain an overview of the working environment, competence, motivation and work performance of the employee at Tanjung Jabung District Education Office; and to know the influence of the working environment andwork motivation against the competencies and performance of pergawai; as well as to know the influence of work motivation on performance. To answer the research objectives, the author uses the theory that studies related to the variable of researchi.e. working environment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
5
1
6
Order By: Relevance
“…Based on the theoretical study above, it can be indicated that motivation does not mediate competence and transformational leadership style on performance. This is not in accordance with the results of research conducted by Rinawati and Ingsih (2014) and Rahim et. al.…”
Section: Motivation Mediates Competence and Transformational Leadership Styles On Teachers Performance (Hypothesis 8)contrasting
confidence: 99%
See 2 more Smart Citations
“…Based on the theoretical study above, it can be indicated that motivation does not mediate competence and transformational leadership style on performance. This is not in accordance with the results of research conducted by Rinawati and Ingsih (2014) and Rahim et. al.…”
Section: Motivation Mediates Competence and Transformational Leadership Styles On Teachers Performance (Hypothesis 8)contrasting
confidence: 99%
“…P-value competence variable on work motivation (KPTNMTVS) is significant with p value of 0,002, T statistic of 2,886 > 1,299 and the original sample is positive, then Ho is rejected and it was concluded that the competence of positive and significant effect on work motivation, if the teachers have good competence in carrying out basic tasks and functions, then the teachers will always have high work motivation in carrying out his work , and vice versa. This is consistent with the research conducted by Rahim et. al.…”
Section: Effect Of Competence On Motivation (Hypothesis 1)supporting
confidence: 94%
See 1 more Smart Citation
“…Vice versa, employees who do not have competence in the field of work will produce work that is sometimes not as expected by the organization. Study (Pinca, 2015), (Rande, 2016), (Ataunur & Ariyanto, 2015), (Setiawati, 2017), (Adam & Kamase, 2019), (Mustikawati & Qomariah, 2020), (Prahiawan, Sultan, & Tirtayasa, 2017), (Rahim, Syech, & Zahari, 2017), (Mananeke, Mandey, & Mufidah, 2014) states that the competencies possessed by employees can improve employee performance. While research (Bahri, Basalamah, Kamse, & Bijang, 2018) states that competence has no effect on employee performance in an organization.…”
mentioning
confidence: 99%
“…Dari hasil penelitian lain yang juga mendukung hasil dari penilitian ini yaitu yang menyatakan bahwa secara parsial variabel kompetensi pegawai berpengaruh secara positif dan signifikan terhadap variabel motivasi pegawai yaitu terdapat pada beberapa penelitian yang dilakukan oleh (Heriswanto 2018;M. Khafit Ashar, Mujanah, and Murgianto 2019;Meidita 2019;Rahim, Syech, and Zahari 2017).…”
Section: Pengaruh Kompetensi Terhadap Motivasi Pegawaiunclassified